(untitled) (Al-Academy, 2022)
The research tagged with the controversy of aesthetic interpretation between the sculptures and their titles in contemporary Iraqi sculpture, “Exhibition of Experiments in Contemporary Iraqi Sculpture as a Model”, and it is one of the new research that contributes to strengthening the critical path in the Iraqi fine movement, as the first chapter dealt with the research problem stemming from the question: What is the impact of the aesthetic hermeneutic controversy between the title and the title in contemporary Iraqi sculpture?, and do the titles of the sculptural works help to understand or enhance their contents?, The research objective included: To identify the controversy of the aesthetic interpretation of sculptures and their titles in contemporary Iraqi sculpture, and the importance of the research was born from the importance of The topic is considered one of the new researches that were not previously researched, as well as being a qualitative addition to the scientific curricula in the field of aesthetic interpretation. The research was determined by objective limits restricted by the concept of(title) and(the title) , and the aesthetic hermeneutic dialectic between them. And with spatial limits: the sculptures displayed in the exhibition 3 X 6, entitled(Experiments in Contemporary Iraqi Sculpture) , at the Akad Art Gallery. Sculptors Reda Farhan, Haitham Hassan, and Najm al-Qaisi. And the time limits in 2022. Then came the definition of the terminology of the concept of the titleAs for the second chapter, it included: the theoretical framework of the research and it has three sections. The first was devoted to studying the topic of the concept of address and its importance, and the second dealt with the topic of types of addresses, while the third included the topic of address functions. As for the third chapter: the procedural framework for the research, it included the research community: the artworks that were presented in the exhibition, and the research sample that was intentionally chosen in proportion to the research objectives, and amounted to three artworks for each sculptor. The researchers relied on observation and indicators in analyzing the sample models using the descriptive analytical approach.1. All artworks in the research community have titles, except for six artworks without titles by artist Reda Alwan, due to the clarity of their visual contents.2. Most of the artworks were made in bronze, except for the works of the sculptor Haitham Hassan, which are made of multiple materials such as wood, glass and bronze, so that this diversity is compatible with the parallel text(the title).3. All samples of the sample employed clear and uncomplicated contents visually, to make it easier for the recipient to interpret these aesthetic contents, except for the works of the artist Najm al-Qaisi, which included a contrast between the title and the title.